A simultaneous gas feeding and cell-recycled reaction (SGCR) system to achieve biomass boosting and high acetate titer in microbial carbon monoxide fermentation. (February 2020) - Lee, Mungyu; Yasin, Muhammad; Jang, Nulee; Chang, In Seop
Graphical abstract: Highlights: Newly designed CO fermenting system was constructed. Simultaneous gas feeding and cell-recycled reaction (SGCR) system was operated. Influential parameters and critical factors were examined for system optimization. Higher biomass (9.7 g/L) and acetate (9.8 g/L) concentration are achieved in SGCR mode. Abstract: This study employed a simultaneous gas feeding and cell-recycled reaction (SGCR) system to ferment CO using Eubacterium limosum KIST612. A bubble column reactor was equipped with an ex-situ hollow fiber membrane module to enable cell recycling. The internal gas circulation rate was adjusted by controlling the pump speed to provide sufficient gas supplement to the microorganism. Gas feedings were conducted by either the use of a gas-tight bag (Batch), a pressurized gas cylinder (Continuous), or a sequential combination of the two (Mixed feeding). Mixed feeding mode achieved higher biomass (9.7 g/L) and acetate (9.8 g/L) concentrations than Batch mode (3.2 g/L biomass and 7.0 g/L acetate) or Continuous mode (5.0 g/L biomass and 8.1 g/L acetate). The high acetate titer in Mixed feeding mode was achieved due to the high concentration of cells secured in a short time at the initial operation stage and maintaining a high specific growth rate.